Correlation between Science Process Skills and Student-Tool Interactions in Surgical Practice and Microscope Observations - Al-Farisi, Fadli Robby; Herlanti, Yanti; Husna, Nida; Hidayat, Dinnisa Haura Zhafira (Jurnal Pendidikan Progresif, 2022)
Correlation between Science Process Skills and Students’ Interaction With Practicum Tools in Surgical Practice and Microscope Observations. Objective: This study aimed to determine whether there was a significant correlation between Science Process Skills (SPS) and Student Interaction with Practicum Tools (SIPT) when the students were conducting Surgical Practice and Microscope Observations in their practicum session.  Methods: The design used for this study was descriptive correlational study with 11th grade high school students with a total of 58 students as the samples. Findings: The data were collected by using test and questionnaire as the instruments then were tested and analyzed using Spearman correlation test and Z test where the results were 0.16 (Spearman) and 1.21 (Z Test), which meant that there was no significant correlation between SPS and SIPT. Conclusion: As the conclusion, between SIPT and SPS, even though there was a mutual connection, it was not significant. One of the reasons was that the learning conditions at the time the research was carried out, the students must learn from home due to Covid-19 Pandemic that lessen the opportunities to learn directly at school. Keywords: student scientific skills, science process skills, motoric skills, practicum, students’ interaction, natural science.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202209